It starts with food - Hartwig, Dallas frey50; Hartwig, Melissa (Las Vegas Victory Belt Pub. ; Enfield : Publishers Group UK [distributor], 2012)
An outline for a clear, balanced, sustainable plan to change eating habits forever. Over the last three years, the Hartwigs' underground Whole30 program has quietly led tens of thousands of people to weight loss, improved quality of life and a healthier relationship with food.
pt. 1. It starts with food. Food should make you healthy -- Our nutritional framework -- pt. 2. Good food standards. What is food? -- Your brain on food -- Healthy hormones, healthy you -- The guts of the matter -- Inflammation: no one is immune -- pt. 3. Less healthy. Sugar, sweeteners, and alcohol -- Seed oils -- Grains and legumes -- Dairy -- It all adds up -- pt. 4. More healthy. Meat, seafood, and eggs -- Vegetables and fruit -- The right fats -- pt. 5. Let's eat! Meal planning made easy -- pt. 6. The Whole30. The Whole30: preface to the program -- The Whole30: process of elimination -- The Whole30: reintroduction -- pt. 7. Whole30, whole life. Strategies for long-term success -- Fine-tuning for special populations -- Supplement your healthy diet -- Appendix A. The meal map. Master recipes: protein and vegetables -- Master recipes: curries and soups -- Finishing touches: sauces, seasonings and dressings -- Quick-and-easy meal: a really great steak -- Quick-and-easy meal: no-fuss salmon cakes -- Fancypants meal: delicious dinner party -- Appendix B. Resources. Weight, volume, and temperature conversions -- Cookbooks and recipes -- Finding good food -- Web sites, books and movies.
Foreword by Luc Readinger.
Keywords: Nutrition; Food habits; Diet therapy; Well-being; Weight loss; Diet therapy; Popular works